Broad line region and black hole mass of PKS 1510-089 from spectroscopic reverberation mapping - Suvendu Rakshit (EDP SCIENCES S A, 2022)
Reverberation results of the flat spectrum radio quasar PKS 1510-089 from 8.5 years of spectroscopic monitoring carried out at Steward Observatory over nine observing seasons between December 2008 and June 2017 are presented. Optical spectra show strong H fi, H gamma, and Fe II emission lines overlying on a blue continuum. All the continuum and emission line light curves show significant variability with fractional root-mean-square variations of 37 :30 +/- 0 :06% ( f5100), 11 :88 +/- 0 :29% (H gamma), and 9 :61 +/- 0 :71% (H beta); however, along with thermal radiation from the accretion disk, non-thermal emission from the jet also contributes to f5100. Several methods of time series analysis (ICCF, DCF, von Neumann, Bartels, javelin, chi(2)) are used to measure the lag between the continuum and line light curves. The observed frame broad line region size is found to be 61:1+4:0 3:2 (64:7+27:1 10:6) light-days for Hfi (H gamma). Using the (sigma)line of 1262 +/- 247 km s 1 measured from the root-mean-square spectrum, the black hole mass of PKS 1510-089 is estimated to be 5 :71+0:62 0:58 +/- 107M